Confronting Globalization
XII, 280 p.
Keywords: Informed by critical theory, the essays in this collection examine the complex dynamics of globalization, the challenges that confront democracy, justice and rights under globalization, and new approaches that seek to contest the excesses of globalization and promote the struggle for global justice. They form a challenging and timely volume that will be essential reading for anyone interested in the normative dimensions of globalization.